2021
DOI: 10.1021/acs.jpcc.0c11425
|View full text |Cite
|
Sign up to set email alerts
|

Recoverability of N4x–Anions to Ambient Pressure: A First-Principles Study ofcyclo- andsyn-Tetranitrogen Units

Abstract: In this paper, we have analyzed the possibility of various neutral and anionic forms of both cyclic and acyclic N4 species to be recovered to ambient conditions using state-of-the-art computational techniques. Phonon dispersion and mechanical properties calculations as well as ab initio molecular dynamics simulations revealed that syn-tetranitrogen units are kinetically stable only in the form of N4 4– anion. Meanwhile, salts of cyclic N4 (c-N4, tetrazete) with alkali, alkaline earth metals, and aluminum appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…In the field of high-energy materials science, the intrinsic properties of reactants are considered fundamental characteristics of high-energy materials. However, the calorific value, serving as a crucial technical parameter, holds significant reference value in assessing the performance of high-energy materials. All salt compounds had a high positive heat of formation (297.8–942.5 kJ mol –1 ), which is significantly higher than that of TNT. According to the calculation of the enthalpy of organic salt formation by the Born–Haber energy cycle, an isobond reaction of anions and cations is first constructed.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of high-energy materials science, the intrinsic properties of reactants are considered fundamental characteristics of high-energy materials. However, the calorific value, serving as a crucial technical parameter, holds significant reference value in assessing the performance of high-energy materials. All salt compounds had a high positive heat of formation (297.8–942.5 kJ mol –1 ), which is significantly higher than that of TNT. According to the calculation of the enthalpy of organic salt formation by the Born–Haber energy cycle, an isobond reaction of anions and cations is first constructed.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular nitrogen allotrope bipentazole (N10) is thermally stable at ambient temperature due to the formation of strongly aromatic pentazole rings . The AIMD simulations revealed that syn-tetra nitrogen units are kinetically stable only in the form of N 4 4– anion whereas syn- N 4 2– anions are not stable at ambient pressure. Due to their low thermal stability, aryl pentazoles convert into cyclo-pentazolate salts by cleaving the C–N bond and the pentazoles are thermally stable up to 77 °C …”
Section: Resultsmentioning
confidence: 99%
“…Metal atoms play a key role in stabilizing nitrogen-bearing polyanions through charge transfer mechanisms at high pressures. Extensive theoretical and experimental investigations have demonstrated that the majority of metals spanning the periodic table, including alkali metals, [10][11][12][13][14][15][16][17][18][19] alkaline-earth metals, [20][21][22][23][24] transition metals, [25][26][27][28][29][30] and rare-earth metals, [31][32][33][34] are capable of engaging in reactions with nitrogen atoms at high pressure (please see the ESI †). This capability facilitates the formation of a diverse range of polynitrogen frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…This capability facilitates the formation of a diverse range of polynitrogen frameworks. Of particular interest are frameworks encompassing a wide array of polynitrogen units, including azides (N 3 À ) as exemplified in alkali metal azides AN 3 (M = Li, Na, K, Rb, or Cs), 10,11,18,[35][36][37] pentazolate (N 5 À ) as observed in MN 5 (M = Li, Na, K, Rb, Cs, Ca, Sr, Ba, Cu, Ta) 15,18,19,[22][23][24][38][39][40] or MN 10 (M = Be, Mg, Ba), 24,41,42 benzene (N 6…”
Section: Introductionmentioning
confidence: 99%